Pendidikan Agama Berbasis Budaya Lokal Papua Suku Kokoda Di Maibo Kabupaten Sorong Dalam Pengenalan Nilai-Nilai Agama Pada Anak - Muhammad Rusdi Rasyid; Efa Rubawati; Rosdiana Rosdiana; Sudirman Sudirman (Al-Riwayah : Jurnal Kependidikan, 2023)
The purpose of this research is; firstly, analyzing and describing forms of local culture-based religious education conducted by the Kokoda Tribe, secondly describing the roles of parents, tribal chiefs and mosque imams in designing forms of religious education with a cultural basis and thirdly, analyzing and describing the challenges and opportunities for Kokoda children's religious education. This research is a qualitative descriptive study that aims to provide a real picture of religious education in the Kokoda tribe in Maibo. The data collection process uses in-depth interviews, documentation, and observation. The research results show that; first, the form of religious education of the Kokoda Tribe through the Syawat Tale tradition which contains stories of the Prophets and Apostles. Second, the role of parents and tribal chiefs in designing forms of religious education by upholding personal communication as a form of ethics and manners in interacting with tribal chiefs or people who are elder and respected. Third, the challenge for Kokoda's children's religious education is that there are no proper learning facilities available